2011
DOI: 10.1002/eji.201041246
|View full text |Cite
|
Sign up to set email alerts
|

IL‐22 in antifungal immunity

Abstract: Deciphering cellular and molecular mechanisms that maintain host immune homeostasis with fungi and the breakdown of this homeostatic tolerance during fungal infections disease is a challenge in medical mycology. In fact, the virulence of fungi may be determined by the interaction between fungi and the host immune status and its classification as a commensal microorganism or a pathogen may shift depending on the balance. In addition to the central role of the IL-12/IFN-c-dependent Th1 responses in cell-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
0
27
0
2
Order By: Relevance
“…The other five patients with the same genotype or heterozygous AIRE mutation had low or undetectable anti-IL-17A antibody levels and were asymptomatic or presented only mild and transient signs of mucocutaneous candidiasis. Previous studies have suggested that IL-22 plays an important role in the protection of skin and epithelial surfaces against Candida infection [6,39]. It has been reported that IL-22-producing cells help to protect mucosal surfaces against fungal infection in conditions of defective adaptive immunity, through a primitive antifungal effector mechanism [6,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other five patients with the same genotype or heterozygous AIRE mutation had low or undetectable anti-IL-17A antibody levels and were asymptomatic or presented only mild and transient signs of mucocutaneous candidiasis. Previous studies have suggested that IL-22 plays an important role in the protection of skin and epithelial surfaces against Candida infection [6,39]. It has been reported that IL-22-producing cells help to protect mucosal surfaces against fungal infection in conditions of defective adaptive immunity, through a primitive antifungal effector mechanism [6,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that IL-22 plays an important role in the protection of skin and epithelial surfaces against Candida infection [6,39]. It has been reported that IL-22-producing cells help to protect mucosal surfaces against fungal infection in conditions of defective adaptive immunity, through a primitive antifungal effector mechanism [6,39]. Furthermore, IL-22 has been reported to play a role in candidiasis, by controlling fungal invasion and epithelial homeostasis [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these reports, it appears that both IL-22 as well as IL-17 are required for full protection against C. albicans infection. The specific role and requirement of each individual cytokine still need further clarification (Zelante et al 2011). …”
Section: Il-22 In Yeast Infectionmentioning
confidence: 99%
“…IL-22 is known to mediate anticandidal resistance at mucosal surfaces under conditions of defective adaptive immunity (Zelante et al, 2011), an activity to which the local microbiota crucially contributes (Zelante et al, 2013). Sensing of tissue damage via the NLRP3 or NLRP6 increased the ratio of IL-22/ IL-22 binding proteins (IL-22BP) via an IL-18-dependent downregulation of IL-22BP, thereby linking the activity of IL-22 to inflammasome activation (Huber et al, 2012).…”
Section: Introductionmentioning
confidence: 99%